Madrasah dan Sistem Pendidikan Islam di Era Globalisasi : Penelitian - Candra Kirana; Abdullah Idi; Karoma; Husnul Amin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article examines the strategic position of madrasahs within the Islamic education system amidst the currents of globalization that demand change, innovation, and high competitiveness. This study highlights how madrasahs, as Islamic educational institutions, maintain their religious identity while simultaneously updating their curriculum and management to ensure relevance to current developments. This research uses a qualitative approach with a literature review method to analyze data from various sources, both classical and contemporary, related to the modernization of Islamic education. The results of the study indicate that globalization brings both challenges and opportunities for madrasahs in strengthening the integration of religious and scientific knowledge, improving the quality of human resources, and expanding the reach of Islamic education through digital technology. By prioritizing the principle of balance between Islamic values ​​and scientific advancement, madrasahs can play a role as centers for character, intelligence, and spirituality formation in the modern era.